A Comparative Analysis of The Social Pension System and The Labor Market: The Case of Romania - Bianca AVRAM-POP; Constantin CUCOSEL (Communications of International Proceedings, 2022)
The phenomenon of the aging population together with the massive emigration of the labour force represent worrying aspects that affect Romania economically and socially. As social pensions are the main types of social insurance in this country, this paper analyzes the evolution of the average number of employees compared to that of pensioners. The analysis continues with the ratio of the average pension to the average salary, but also to the price index. The study of these indicators is carried out for a period of 30 years, from 1990 (after the fall of the communist regime in 1989) to 2019 inclusively. The results of the research are important both for the academic community and for the political decision makers.
Keywords: public pension system; sustainability; demographic tendency; trends; pillar I pension